Portrait of a CAF: The story of cancer-associated fibroblasts in head and neck cancer. (November 2020) - Custódio, Marcos; Biddle, Adrian; Tavassoli, Mahvash
Highlights: CAFs are heterogenous cells but only subtypes expressing α-SMA are known. CAF-secreted exosomes carry microRNA that change cancer cell behaviour. CAF-metabolism is context-dependent and rely on the interaction with cancer cells. CAFs affect immune cells through direct and indirect mechanisms. There is little information about CAFs derived from HPV positive tumours. Abstract: Complex interactions take place during cancer formation and progression. In this regard, there has been increasing focus on the non-malignant cells that make up the tumour microenvironment (TME), and how they interact with malignant tumour cells. TME is highly heterogeneous and has a major influence on tumour behaviour and therapy response. Cancer-associated fibroblasts (CAFs), one of the main components of the TME, establish dangerous liaisons with cancer cells and other components of the TME to shape a tumour-supportive environment in many types of cancer. Head and neck squamous cell carcinoma (HNSCC) encompass the malignant neoplasms arising from the mucosal lining of the oral cavity, pharynx and larynx. The TME of HNSCC contributes to tumour progression and this stromal compartment may be an interesting target for treatment. There is an emerging picture of the behaviour of CAFs in HNSCC; how they affect and are affected by the TME. We aim to summarise and discuss the current understanding of CAFs in head and neck cancer, exploring CAF activation and heterogeneity, and interaction with cancer cells and other cells within the TME.